Colorectal cancer incidence in 5 Asian countries by subsite: An analysis of Cancer Incidence in Five Continents (1998–2007). (December 2016) - Park, Hye-Min; Woo, Hyeongtaek; Jung, Sun Jae; Jung, Kyu-Won; Shin, Hai-Rim; Shin, Aesun
Highlights: We estimated cancer incidence of proximal colon and distal colon and compare distribution of colorectal cancer incidence by subsite across 5 Asian countries. We observed trend of increasing colorectal cancer incidence in Asian countries is mainly due to the increase of colon cancer, not rectal cancer. Proportion of rectal cancer out of total colorectal cancer notably varies in Asian countries. Abstract: Colorectal cancer is the fourth most common cancer in Asia. However, the trends in colorectal cancer incidence by subsite have not been analyzed across Asian countries. We used the most recent, high quality data from 6 cancer registries for two 5-year periods, 1998–2002 and 2003–2007, from Cancer Incidence in Five Continents to estimate colorectal cancer incidence by subsite in 5 Asian countries. Cases with overlapping lesions or otherwise unspecified colon cancer were re-distributed as proximal or distal colon cancer. Age-standardized incidence rates (ASRs) per 100, 000 population and incidence rate ratios from 1998 to 2002 to 2003–2007 were calculated for each subsite. For 2003–2007, men in Miyagi, Japan, had the highest ASR for cancer in the proximal colon, distal colon and rectum. Men of Jewish ancestry in Israel had a high ASR for proximal and distal colon cancer, but the lowest ASR for rectal cancer. The proportion of rectal cancer was highest among Korean men (51.39%) and lowest among Israeli women (26.6%). From 1998–2002 to 2003–2007, rectal cancer incidence did not significantly change in most registries, except for men in Miyagi, Japan, and both sexes in Korea. However, during the same period cancer incidence in the proximal and distal colon increased in most registries. In conclusion, there was substantial variation in subsite distributions of colorectal cancer in Asian registries and increases in overall incidence of colorectal cancer could be attributed to increases in colon cancer.